2021
DOI: 10.1186/s41983-021-00269-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of epileptiform brain activity and specific language impairment (SLI) in preschool children

Abstract: Background Epileptiform activities can cause transient or permanent deficits that affect the children during development and may be accompanied by neurodevelopmental disorders like specific language impairment. Objectives The objective of this study was to find if there is a possible association and the impact of epilepsy and epileptiform activity in children with specific language impairment. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The difference reached statistical significance in the Combinatorial Receptive Language subscale on Months 3, 6, 12, 15, 18, and 21; in the Expressive Language subscale on Months 9 through 36 (with the exception of Month 30); in the Sociability subscale on Months 6 through 36 (with the exception of Month 30); in the Sensory awareness subscale on Months 3, 9, 24, 30, and 36; in the Health subscale on all time points except month 3. The results of this study support previous reports of a negative correlation between the presence of seizures and every aspect of a child’s development (Esmael et al, 2021; Hermann et al, 2002; Schoenfeld et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference reached statistical significance in the Combinatorial Receptive Language subscale on Months 3, 6, 12, 15, 18, and 21; in the Expressive Language subscale on Months 9 through 36 (with the exception of Month 30); in the Sociability subscale on Months 6 through 36 (with the exception of Month 30); in the Sensory awareness subscale on Months 3, 9, 24, 30, and 36; in the Health subscale on all time points except month 3. The results of this study support previous reports of a negative correlation between the presence of seizures and every aspect of a child’s development (Esmael et al, 2021; Hermann et al, 2002; Schoenfeld et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Hermann et al found that children with early onset of seizures scored 11.6% lower on WAIS-III Verbal IQ scores ( p <0.0001), 11.3% lower on the Boston Naming Test ( p <0.0001), and 21.2% lower on the Controlled Oral Word Fluency test ( p =0.002) as compared to a healthy age-matched controls (Hermann et al, 2002). Esmael et al found that children with selective language impairments had a 26.2% prevalence of abnormal EEGs compared to 6.2% in the age- and sex-matched control group ( p =0.006) (Esmael et al, 2021). There was a strong negative correlation between language intelligence quotient and abnormal EEGs (r=-0.91, p<0.01).…”
Section: Introductionmentioning
confidence: 99%
“…However, this exclusion criterion fails to account for children who have both language difficulties and a non-verbal IQ score below 85 but have not scored low enough to be diagnosed with an intellectual disability (Volkers, 2018). Thus, SLI may be seen as a more artificial abstraction intended for research, such as brain imaging (e.g., Esmael et al, 2021), and genetic studies (e.g., Eldesouki, 2021) where identification of 'pure' language impairment may be warranted, and not for clinical purposes nor to inform social health policy (Reilly et al, 2014;Tomblin et al, 1996). Further, evidence indicates that having average or low average IQ does not contribute to differences in functional impact or education attainment of children with DLD (Norbury et al, 2016a(Norbury et al, , 2016b, nor does it influence responsiveness to intervention (Bishop et al, 2016;Bowyer-Crane et al, 2011;Ebbels, 2013).…”
Section: Introductionmentioning
confidence: 99%